KINERJA KARYAWAN DITINJAU DARI KONDISI DAN MOTIVASI KERJA PADA KARYAWAN PT. PELABUHAN INDONESIA IV (PERSERO) CABANG MAKASSAR - Rudi Alfriyan; Aswar Aswar (BJRM (Bongaya Journal of Research in Management), 2020)
This study aims to examine and analyze the Effect of Working Conditions and Work Motivation on the Performance of PT. Pelabuhan Indonesia IV (Persero)Makassar Employees. Data collection using primary data with Questionnaire Technique whose population was obtained from all PT. Pelabuhan Indonesia IV (Persero)Makassar employees by using the Slovin formula, amounting to 73 employees. The results of the questionnaire have been tested for validity and reliability, also tested for classic assumptions in the form of assumptions of Normality, Multicollinearity Assumptions, Heteroscedasticity, and Autocorrelation. The method of data analysis uses multiple regression techniques. Based on the results of the analysis, it turns out that the results of the study indicate that the first hypothesis is accepted because it shows the results of the hypothesis test that there is a significant positive effect. Means Working Conditions contributes significantly to employee performance. The second hypothesis is accepted because it shows a significant positive hypothesis test result. Means Motivation contributes significantly to employee performance. The third hypothesis is accepted because Working Conditions and work motivation have a significant positive effect simultaneously on employee performance.